Effects of Trimetazidine Combined with Atorvastatin on Cardiac Function in Patients with Stable Angina Pectoris of Coronary Heart Disease - Zhang N; Ren Y; Qin D; Yang X; Chen Z; Zhao L (International Journal of General Medicine)
Na Zhang,1 Yuanyuan Ren,1 Donghui Qin,2 Xue Yang,1 Zhuo Chen,1 Li Zhao1 1Department of Cardiology, The Third Affiliated Hospital of Qiqihar Medical College, Qiqihar, Heilongjiang Province, People’s Republic of China; 2Department of Pharmacy, The Second Hospital of Qiqihar, Qiqihar, Heilongjiang Province, People’s Republic of ChinaCorrespondence: Li Zhao, Email zgc016@126.comObjective: Growing evidence suggests that metabolic modulation combined with lipid-lowering therapy may provide synergistic benefits in coronary heart disease (CHD). This study aimed to evaluate the effects of trimetazidine combined with atorvastatin on cardiac function and inflammatory responses in stable angina pectoris.Methods: This retrospective study analyzed 100 CHD patients with stable angina (2019 ESC criteria) treated at the Third Affiliated Hospital of Qiqihar Medical College from 2021– 2024. Patients were categorized into two groups based on prescription records, control group (n=50), receiving atorvastatin 20 mg/day, and an observation group (n=50), receiving atorvastatin 20 mg/day plus trimetazidine 20 mg TID. Outcomes included angina characteristics, lipid profile, endothelial function (NO/ET-1), specified inflammatory markers (hs-CRP, TNF-α), cardiac function (LVEF, NT-proBNP), and safety.Results: The observation group had a significantly higher overall response rate (94.0% vs 80.0%, P< 0.05). Both groups showed reduced angina frequency and duration post-treatment, with more pronounced improvements in the observation group (P< 0.05). Chest pain severity (VAS) also decreased more significantly in the observation group, indicating superior efficacy (P< 0.05). Lipid metabolism improved in both groups, with greater reductions in TC, TG, and LDL-C and a more substantial HDL-C increase in the observation group (P< 0.05). Endothelial function markers improved, with lower ET-1, TNF-α, and hs-CRP levels and higher NO levels, showing more significant changes in the observation group (P< 0.05). Cardiac function parameters improved in both groups, with greater reductions in LVEDD and NT-proBNP and greater increases in LVEF and 6MWD in the observation group (P< 0.05). Adverse effects were low and comparable between groups (8.0% vs 6.0%, P> 0.05).Conclusion: The trimetazidine-atorvastatin combination demonstrates synergistic effects in improving angina symptoms, lipid metabolism, and cardiac function in stable CHD, with additional benefits in endothelial protection and measured inflammatory regulation. These findings support its consideration as adjunctive therapy, though further validation of broader inflammatory impacts is warranted.Keywords: trimetazidine, atorvastatin, stable angina pectoris, coronary heart disease, cardiac function, inflammatory regulation